ANALISIS PENGARUH RETURN ON EQUITY, FIRM SIZE, FREE CASH FLOW, INVESTMENT OPPORTUNITY SET, DAN DEBT RATIO TERHADAP DIVIDEND PAYOUT RATIO (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2011-2014) - Hesti Secsio, Esa Nursanti Dwi; Prasetiono, Prasetiono (Faculty of Economics and Business Diponegoro University, 2016)
The values of Return on Equity, Firm Size, Free Cash Flow, Investment Opportunity Set, and Debt Ratio in manufacturing companies fluctuate annually during the research period. The fluctuation is the opposite of the increase on Dividend Payout Ratio during the year of 2011 to 2014. Due to the said phenomena gap, this research aims to test the effect of ROE, firm size, free cash flow, investment opportunity set, and debt ratio of dividend payout ratio of Manufacturing Companies listed on IDX during the period of 2011-2014.The sample employed in this research selected by purposive sampling method which contains of 22 companies fitting the criteria set during the period of 2011-2014. The data is obtained based on the published annual report and financial report. The method of analysis employed is regression with least squares equation and the hypothesis is tested by using t-statistic to reveal partial regression coefficient as well as F-statistic to test the simultaneous effect with confidence level at 5%.The result reveals partial result that free cash flow affect DPR positively and significantly. ROE, firm size, and investment opportunity set affect positively but non- significantly on DPR. Meanwhile, Debt Ratio affect negatively and non-significantly on DPR. Simultaneously, ROE, firm size, free cash flow, investment opportunity set, and debt ratio affect DPR significantly. The result of regression estimation reveals the prediction competence from the 5 independent variable on DPR is at 11.9% meanwhile the other 88.1% is affected by other factors which are not included in this research.